Kindergarden management system for Taska Anakku Comel UMP - Azira, Yacob (2012)
This project is about kindergarten management system (KMS) that will transfer manual system to computerized system. This system focused on staff and teacher task.This system will use RAD methodology in development process.Tools will be used are Adobe Dreamweaver CS3 as system interface development and XAMPP as database platform.This system is generating as to accomplish the objectives that are to develop a prototypes of kindergarten management system,to centralized a database in manage modules teachers,students and staff information and to produce documentation and report generation.There are seven modules in this system, registration,student record,event,news,fees,Q&A Session and activity.Staff will manage the student and teacher registration,event,fees,news,Q&A Session and activity. Teacher can manage student registration,student attendance, view event and student record.For public user,they can view student activities,news and ask question at the contact interface.The question will sent to staff and staff will reply the message.Public can view the response from staff at the Q&A interface.